Equatorial and low latitude ionospheric effects during sudden stratospheric warming events: Ionospheric effects during SSW events - Chau Chong Shing, Jorge Luis; Goncharenko, Larisa P.; Fejer, Bela G.; Liu, Han Li (Space Science Reviews, 2012)
There are several external sources of ionospheric forcing, including these are solar wind-magnetospheric processes and lower atmospheric winds and waves. In this work we review the observed ion-neutral coupling effects at equatorial and low latitudes during large meteorological events called sudden stratospheric warming (SSW). Research in this direction has been accelerated in recent years mainly due to: (1) extensive observing campaigns, and (2) solar minimum conditions. The former has been instrumental to capture the events before, during, and after the peak SSW temperatures and wind perturbations. The latter has permitted a reduced forcing contribution from solar wind-magnetospheric processes. The main ionospheric effects are clearly observed in the zonal electric fields (or vertical E×B drifts), total electron content, and electron and neutral densities. We include results from different ground- and satellite-based observations, covering different longitudes and years. We also present and discuss the modeling efforts that support most of the observations. Given that SSW can be forecasted with a few days in advance, there is potential for using the connection with the ionosphere for forecasting the occurrence and evolution of electrodynamic perturbations at low latitudes, and sometimes also mid latitudes, during arctic winter warmings. Por pares